Cannibalism and Gang Involvement in the Cinematic Lives of Asian Gangsters - Caires, Richard J. De; Lankin, Paul T.; Shon, Phillip C (International Journal of Criminology and Sociology, 2012)
Previous works focusing on Asian organized crime groups have examined the history, structure, function, and the extent of their legal and illegal business enterprises. While credible, such a line of inquiry omits crucial information on the source and reasoning behind membership and affiliation for members in Asian organized crime groups, such as the “Jok-Pok”, Triads, and Yakuza. Due to the secretive nature of those organized crime groups, such an omission leaves a major gap in the understanding as to why Asian youths join gangs. This paper examines the prevailing characteristics of membership and affiliation within Asian gangs by analyzing Asian gangsters in Asian (Chinese, Japanese, Korean) cinema. Results indicate that the lure of economic benefits, exposure to gang life from within one’s family and lack of opportunities to achieve legitimate goals constitute the three most pervasive themes that define membership within Asian gangs as represented in popular cinema.